Virtual musculo-skeletal model for the biomechanical analysis of the upper limb - Pennestry, E.; Stefanelli, R.; Valentini, P. P.; Vita, L. (Journal of Biomechanics, 2007)
In this paper, a musculo-skeletal model of the upper limb is presented. The limb is modelled as a three-dimensional 7 degrees-offreedom system, linked to the shoulder, which has been considered as frame. The upper limb model is made up of four links corresponding to the most important body segments: the humerus, the ulna, the radius and the hand, considered as a single rigid body. Particular attention has been paid to the modelling of joints in order to mimic all the possible arm and forearm movements (including prono-supination). The model also includes 24 muscles. The mathematical model used to describe the muscles is that proposed by Zajac in 1989, modified by the authors. The kinematic analysis has been performed including an ergonomics index to take into account the posture and joint physical limits. Moreover an optimization criterion based on minimum activation pattern has been included in order to find muscular activation coefficients. The results of the proposed methodology concerning muscular activations have been compared to those coming from processed EMG signals, which have been acquired during experimental tests.